Endosperm Balance Number and the polar-nuclei activation hypotheses for endosperm development in interspecific crosses of Solanaceae and Gramineae, respectively - Katsiotis, Andreas; Hanneman, Robert E.; Forsberg, Robert A. (My University, 1995)
The Endosperm Balance Number (EBN) and the polar-nuclei activation (PNA) hypotheses have been developed to interpret, explain and predict interspecific and interploidy crossabilities in the Solanums and the Gramineae, respectively. Although these two hypotheses evolved independently, they share a number of common features. Assignment of EBNs and 'activation/response values' (AVs/RVs) depend on plumpness, size, and germinability of hybrid seeds. Also, both hypotheses emphasize the importance of a balanced parental genic contribution for the normal development of endosperm. However, in the EBN hypothesis a 2 maternal∶1 paternal EBN ratio is a prerequisite for successful interspecific crossability, while the PNA hypothesis is based on the stimulative strength of the male nuclei to initiate mitotic divisions in the primary endosperm nucleus and is idependent on a 2∶1 ratio between the RV of the polar nuclei and the AV of the male gamete. Differences and similarities betweeen the EBN and PNA hypotheses are summarized and contrasted. It is proposed that EBN and PNA be considered as the same concept.
Keywords: Endosperm development; Evolution; Imprinting; Incompatibility; Reciprocal crosses